Kajian Historis dan Isu-isu Kontemporer untuk Merumuskan Agenda Masa Depan Ilmu Administrasi Publik - Agus Pramusinto; Wahyudi Kumorotomo; Erwan Agus Purwanto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2005)
Historically, the study of public administration starts with the endeavors to establish the effective and efficient administration. This followed by the notions of equity values in managing public administration that lead to the idea of the new public administration. Recent challenges such as privatization, multiculturalism, democratization, decentralization and various disasters that occur have produced the demands to pay attention the new look of public administration. This article discusses the history and contemporary issues of public admihistration in order to reformulate the scope of public administration study.